Association between sociodemographic characteristics and quality of life domains in nursing professionals - Karla Gualberto Silva; Célia Regina da Silva Medeiros; Samira Silva Santos Soares; Denise Consuello Araújo dos Santos; Norma Valéria Dantas de Oliveira Souza; Sheila Nascimento Pereira de Farias (Universidade Federal do Ceará, 2020)
Objective: to analyze the association of sociodemographic variables and the domains of the Abbreviated Quality of Life Assessment Instrument (WHOQOL-Bref) in nursing professionals. Methods: cross-sectional study, carried out with 85 nursing professionals of the Family Health Strategy program. Data collection was performed using the sociodemographic form and the WHOQOL-Bref. Sociodemographic data were analyzed using descriptive statistics and the WHOQOL-Bref went through analysis of variance, Student's t test, and Tukey's multiple comparison test. A significance level of 5% was adopted. Results: in the association between sociodemographic characteristics of nursing professionals and the WHOQOL-Bref, a statistically significant association was evidenced for the environment domain, when associated with family income. Conclusion: professionals with lower incomes tend to have a better quality of life.